Capital Structure, Growth and Profitability: A Case of Nepalese Commercial Banks - Sunuwar, Rebika; Dhakal, Padam; Neupane, Pragya; Joshi, Prakash; Adhikari, Radhika; Shah, Rakesh; Dahal, Gangadhar (Nepalese Journal of Economics, 2025)
This study examines the impact of capital structure and growth on the profitability of Nepalese commercial banks. Return on assets and return on equity are the selected dependent variables. The selected independent variables are debt to equity ratio, debt to asset ratio, asset growth, loan to deposit ratio and capital adequacy ratio. The study is based on secondary data of 16 commercial banks with 128 observations for the study period from 2016/17 to 2023/24. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of capital structure and growth on the profitability of Nepalese commercial banks. The study showed that capital adequacy ratio has a positive effect on return on assets and return on equity. It indicates that increase in capital adequacy ratio leads to increase in return on assets and return on equity. Likewise, debt to assets ratio has a negative effect on return on assets and return on equity. It indicates that increase in debt to assets ratio leads to decrease in return on assets and return on equity. However, the study showed that loan to deposit ratio has a negative effect on return on assets and return on equity. It reveals that increase in loan to deposit ratio leads to decrease in return on assets and return on equity. Similarly, debt-to-equity ratio has a positive effect on return on assets. It indicates that higher the debt-to-equity ratio, lower would be the return on assets. Similarly, asset growth has a positive effect on return on equity. It indicates that increase in asset growth leads to increase in return on equity. The result also reveals that deposit growth has a positive effect on return on assets. It indicates that increase in deposit growth leads to increase in return on assets.